The Kinetics of Ethanol Volume Change With Variation of Input Volume and Heating Temperature in The Re-Distillation Process of Glucomannan Extraction Residue Using Batch Distillator - Saut Edo Riko Manurung; Rizky Qhasim Pratama; Sri Rahayoe; Joko Nugroho W. K; Febryan Kusuma Wisnu (The University of Lampung, 2022)
Ethanol is commonly used as a solvent in extracting glucomannan from Porang. However, the extraction process often leaves ethanol. The remaining ethanol can be re-distilled to save the use of it. The remaining ethanol is used in the re-distillation process with input volumes of 50L and 100L with variations in heating temperatures of 80°C, 85°C, and 90°C. This study aimed to analyze the effect of the ethanol input volume and temperature on the output volume of re-distilled ethanol and determine the constant change in volume of re-distilled ethanol using kinetics and Arrhenius equations. The results showed that the input volume and heating temperature variation differed significantly from the ethanol output volume. The k value changes in the ethanol output volume from re-distillation with an input volume of 50L and a temperature variation of 80°C, 85°C, and 90°C respectively were 0.0016, 0.0023, and 0.0027 L/min, while the input volume of 100L was 0.0009, 0.001, and 0.0014 L/min. The results of the k value as a function of temperature using the Arrhenius equation showed that the re-distillation process with an input volume of 50L and 100L produces activation energy (Ea) of 55.83 kJ/mol and 46.94 kJ/mol, while the collision frequency value (A) of 3.03x105/min and 7.7x103/min.Keywords: Distillation, ethanol, glucomannan, arrhenius model, re-distillation